Customary Practices of Sharing Inheritance: An Analysis of Society Practices in Pidie Aceh Darussalam - Zaitun Muzana; Jasni Bin Sulong; Faisal Husen Ismail (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2016)
Handling inheritance from a deceased person is one of important matters that must be performed by the surviving heirs. However, the practice varies in communities, especially in areas affected by customary practices. The wealth of inheritance from the deceased is not only used as payment of funeral expenses and to be distributed to the heirs, but also used for the purpose of fidyah (compensation) for prayers left and others set in indigenous communities. The issue of tradition is important to study and clarify to society because it is not recognized in Islamic teachings and can even lead to diminishing the rights of others. Thus, this study aims to examine the extent of customary practices would affect the principle of inheritance distribution in the society of Pidie, Aceh, Indonesia.